Pengaruh Metode Latihan Drill Terhadap Ketrampilan Sepak Bola Di Academy Ebod Jaya Kebumen Kelompok Umur 10 -12 - Ahmad Syarif; M Bangkit Rizky Pangestu (Mathematics Education Study Program, 2025)
Sports are important activities that must be done by humans in order to obtain physical health. Sports are also a means to support the health of a person's soul and body. Football is a game played by two teams, each team consisting of eleven players, commonly called a team. Football is a sport that is loved by all levels of society, from children to adults. It can be concluded that the purpose of this study is to determine the effect of the Drill training model on the soccer playing skills of students at the Ebod Jaya Kebumen Academy in the Age Group 10-12 Years. And the type of research is quantitative experimental research, namely a type of research that aims to test the causal relationship between the variables studied in this study. The population and sample in this study were all participants at the Ebod Jaya Kebumen Academy aged 10-12 years with a total population of 45 students. The research sample was taken randomly, where 30 participants were selected as a sample consisting of two groups: the experimental group (15 participants) who would receive the fun learning method, and the control group (15 participants) who would use the traditional training method. by using the Research instrument is a tool or facility used by researchers in collecting data so that their work is easier and the results are better, in the sense of being careful, complete, and systematic so that it is easy to process and Data collection in this study is by developing a proficiency test and getting post-test results or not yet applied drill ball skills can be known soccer playing skills of SSB Ebod Jaya Kebumen students in the 10-12 year age group pretest entered the very good category as many as 0 students (0%), good category as many as 1 student (3%), and getting post-test results or already applied drill ball skills soccer playing skills of SSB Ebod Jaya Kebumen students in the 10-12 year age group who entered the very good category as many as 16 students (53%), good category as many as 11 students (37%), sufficient category as many as 4 students (13%) and in the less category there were 0 students (0%) and in the very less category there were 0 students (0%).